Association between the rs1042522 polymorphism in TP53 and prostate cancer risk: An updated meta‐analysis. Issue 2 (25th June 2017) - Fan, Song; Hao, Zong‐Yao; Zhang, Meng; Liang, Chao‐Zhao
Abstract: Objective: The proposal of the present study was to investigate whether the TP53 rs1042522 polymorphism confers susceptibility to prostate cancer (PCa), by performing an updated meta‐analysis. Methods: Eligible publications investigating the association between the TP53 rs1042522 polymorphism and PCa susceptibility were selected from PubMed, Google Scholar, and Web of Science. We used STATA 12.0 software to conduct the analyses. Odds ratio ( OR ) with 95% confidence interval ( CI ) was calculated. Results: A total of 17 case–control studies were retrieved reporting a total of 2683 cases and 2981 controls. However, no significant association was uncovered between the TP53 rs1042522 polymorphism and PCa susceptibility in the overall population under the five genetic models. In the stratification analysis by source of control, an increased susceptibility to PCa was identified in the population‐based (P‐B) group (CG vs. GG: OR  = 1.48, 95% CI : 1.24–1.77, P  < 0.01; CC/CG vs. GG: OR  = 1.32, 95% CI : 1.12–1.57, P  < 0.01), whereas a decreased susceptibility was uncovered in the hospital‐based (H‐B) group (CG vs. GG: OR  = 0.67, 95% CI : 0.46–0.96, P  = 0.03; CC/CG vs. GG: OR  = 0.67, 95% CI : 0.46–0.99, P  = 0.04) under heterozygous and dominant model. Conclusion: This study did not find an association between the TP53 rs1042522 polymorphism and PCa susceptibility in the overall population and corresponding subgroup analyses except in the stratification analysis by source of control. The results suggest that the TP53 rs1042522 polymorphism is not a risk factor for PCa.